Current methodologies to the analysis of morphine and its metabolites in biological matrices - Shan, Xiaoyue; Yang, Bingsheng; Zhang, Ling; Shao, Ji; Jin, Yan; Qiu, Jiayi; Tan, Siwei; Ye, Haipeng; Le, Yanna (Frontiers in Analytical Science, 2026)
Morphine (MOR) is a commonly utilized opioid analgesic in the field of pain management. However, its potential for abuse presents substantial public health concerns. This suggests the necessity for developing an accurate and sensitive analytical method for the determination of MOR and its metabolites in biological specimens. In this review, various analytical techniques, including HPLC, LC-MS, UHPLC-MS and electrochemical sensors, have been applied for the measurement of MOR and its metabolites in biological samples. LC-MS is the gold standard due to its high sensitivity and specificity. In addition, electrochemical methods are also highlighted as a primary analytical approach in this research.